Diseño interior del bar de la discoteca K’OS aplicando un estilo moderno contemporáneo - Ludeña Preciado, Nixon Ivan (2015)
The design and interior decoration is today performed to achieve a nice atmosphere, comfortable, comfortable and cozy especially, in order to improve the environment in which people are involved in the best possible way. Consider the above points and the proper application of the knowledge acquired both theoretical and practical, in the project called "INTERIOR design for the K Club BAR'OS by applying a contemporary modern style". Which seeks to provide alternatives for design and decoration of Exchange and trade centres such as bars. The service offering karaoke bar was considered implementing sanitary batteries and relocate the bar and furnishings with a suitable distribution according to what is the karaoke bar, this project presents a linear and simple design little loaded with lighting suitable for general comfortable environment, reflecting confidence and safety for customersBAR